Improvement of the technology of manufacturing rolling smoking tobacco with specified consumer characteristics based on principles of food combinatorics - A. G. Mirgorodskaya; M. V. Shkidyuk; O. K. Bedritskaya (Новые технологии)
The article is devoted to establishing the dependence of consumer characteristics of smoking tobacco on the ingredient composition of tobacco blending and technological properties.